Estudios sobre el África romana : culturas e imaginarios en transformación - Salcedo, Fabiola; Lázaro, Estefaniá Benito; España-Chamorro, Sergio (Archaeopress Roman archaeology, 2018)
These collected papers are for those who have their gaze fixed on the fascinating mosaic of cultures that was the North-African world from the moment Rome appeared in the region. Most articles are dedicated to the world of images, but other subjects include Historiography, Archaeology of Architecture, and Libyan-Berber ethnicities.